(untitled) (Research, Society and Development, 2021)
This work was carried out at school in a public school in Sinop, Mato Grosso, Brazil, in 2011 and aims to identify how the process of development develops. teaching and learning and the problems faced by teachers. For this, bibliographic and field research was carried out with a sample of teachers and students who teach and attend school, respectively, and questionnaires with open and closed questions were applied. The information obtained from this survey, provided data on the real problems present in Youth and Adult Education. Through the questionnaires applied to the students it was found that 57% belong to the female sex and 43% belong to the male sex. When questioning students as to why they no longer attended regular education, the highest rate was 44.44% for having to help the family economically, followed by 30.30% quitting regular school due to family problems, 18.18% other reasons, 4.04% did not answer, 2.02% was due to school failure, 1.01% did not stop studying. Of the reasons that led the interviewed students to return to study, the highest index was the personal achievement, which was 44.44%, followed by 35.35% who intend to acquire a job, 12.12% other reasons, 7, 07% remain in employment, 1.01% chose not to respond. From the answers, it is concluded that the CEJA SILVA FREIRE school seeks to serve students respecting their culture and life history.